Predictors of nursing workers' intention to leave the work unit, health institution and profession - Maiara Bordignon; Maria Inês Monteiro (Universidade de São Paulo, 2019)
Objective: to identify the factors related to the nursing workers' intention to leave the work unit, health institution and profession. Method: cross-sectional study with quantitative approach was carried out with 267 nursing workers from seven emergency units in Brazil. For data collection, we used the Questionnaire of socio-demographic, life style and work and health aspects as well as the Work Ability Index, Workplace violence questionnaire, questions about intention to leave and the Turnover Intention Scale. The predictors of intentions to leave were evaluated through Poisson regression models. Results: workplace violence increased and better satisfaction with current job decreased the probability of greater intention to leave the unit, institution and profession. Better work ability decreased the probability of greater intention to leave the unit and profession. The more qualified workers and those who had been working in the institution longer was more likely to greater intention to leave the profession. Conclusion: promoting job satisfaction, work ability and a violence-free environment is possible to decrease the workers' intention to leave the job or profession, but nursing managers need to understand the three phenomena of intention to quit individually for retention strategies.